Quercetin nanoparticles as a therapeutic approach: pharmacological actions and potential applications in therapy - Reham Farouk El-Sayed Baiomy (BioTechnologia)
The utilization of quercetin nanoparticles as a novel therapeutic strategy has garnered significant attention in recent years. These nanoparticles offer a unique approach to enhancing delivery and effectiveness while overcoming the drawbacks of quercetin. By exploiting the advantages of nanotechnology, such as increased stability and improved bioavailability, quercetin nanoparticles hold significant potential for developing innovative treatments across various medical fields. Quercetin nanoparticles have emerged as an indispensable component in numerous pharmaceutical and medicinal formulations. They are recognized for their anticancer, antitumor, anti-inflammatory, and antidiabetic properties, making them valuable in addressing allergic reactions, metabolic disorders, inflammatory disorders, cardiovascular diseases, and arthritis. From a pharmacological perspective, quercetin nanoparticles have demonstrated beneficial effects against Alzheimer’s disease, primarily through their inhibitory impact on acetylcholinesterase. Furthermore, these nanoparticles have been scientifically documented to possess antioxidant, anticarcinogenic, hepatoprotective, and cytotoxic activities. This comprehensive review aims to explore the pharmacokinetics and biological activities associated with quercetin nanoparticles. It also highlights their potential as therapeutic agents in treating a wide range of diseases, including Alzheimer’s disease, cancer, and neurodegenerative disorders.